Analisis Strategi Pengembangan Bisnis Jasa Boga Menggunakan Analisis Swot dengan Analytic Hierarchy Process - Ghaitsa Zahira Shofa; Danang Indrajaya; Arien Arianti Gunawan (Jurnal Syntax Admiration, 2024)
The existence of MSMEs in Indonesia has spread in various regions, one of which is the Cikarang area. Food Service Company is one of the businesses with high opportunities in Cikarang, PT Buana Boga Catering is a food service business in Cikarang that focuses on running catering for industrial employees, because this company prioritizes target consumers who are in the area around the Cikarang Industrial Estate. PT Buana Boga Catering must continue to innovate in order to survive from existing competitors. The purpose of this study is to analyze the company's development strategy and provide recommendations for new business strategies to create new value that can help PT Buana Boga Catering maintain its business. In this study the authors used the Mix Method research method, namely, utilizing qualitative methods together with quantitative methods, using SWOT analysis and Analytic Hierarchy Process to evaluate it. Based on the research conducted, the results show that there are several alternative business development strategies with the main priority being the use of alternative raw materials that are more suitable in terms of price and availability so as to maintain production costs and increase profits.